Peranan Modal Sosial Terhadap Pengembangan Sistem Agroforestri di Kabupaten Bulukumba - Andi Khairil A.Samsu; Syamsuddin Millang; Muhammad dassir (Fakultas Kehutanan, Universitas Hasanuddin, 2019)
Agroforestry is a concept of sustainability that has various aspects in the implementation and the social capital is one of the important aspect. This study aims to explain how social capital is applicable in community agroforestry management In Kahayya Village, Kindang Sub-district, Bulukumba District. This research uses descriptive qualitative method by using questionnaire method and structured interview with 93 respondents (farmers) who manage the land by agroforestry method. The results indicate that some aspects of social capital, such as social institutions and the level of public confidence shows good value, will be treated in terms of social networking is still showing a bad condition. The level of social capital in agroforestry management in Kahayya Village is at the elementary level of social capital. This can be seen from the condition of the community in the village of Kahayya that still tends to individual welfare but in some cases they are still able to cooperate with other communities if conditions can be mutually beneficial. Such social capital conditions may be used by relevant Institutions and agencies to support sustainable land management through agroforestry patterns as well as institutional strengthening which aims to further increase social capital under adverse criteria.